Microneedle‐Based Local Delivery of CCL22 and IL‐2 Enriches Treg Homing to the Skin Allograft and Enables Temporal Monitoring of Immunotherapy Efficacy. (24th May 2021) - Puigmal, Núria; Dosta, Pere; Solhjou, Zhabiz; Yatim, Karim; Ramírez, Cynthia; Choi, John Y.; Alhaddad, Juliano B.; Cosme, Ana Paula; Azzi, Jamil; Artzi, Natalie
Abstract: Skin allografts only serve as temporary dressing for patients suffering major burns due to their high immunogenicity and rejection by the immune system, requiring systemic immunosuppressive therapies that lead to deleterious side effects. Microneedle arrays composed of hyaluronic acid (HA) and placed on skin allografts can locally deliver immunomodulators and simultaneously sample immune cells in interstitial fluid to monitor the response to the therapy. The cells can be retrieved from the microneedles for downstream analysis by degrading the HA using a reducing agent. Using an allogeneic skin transplantation model, it is shown that the microneedle‐mediated local delivery of the chemokine CCL22 (to attract Tregs ) and the cytokine IL‐2 (to promote their expansion) increases the local immune suppression in the allograft. Moreover, immune cell population in the allograft correlates with that seen in the microneedles. The delivery and sampling functions of the microneedle arrays can help regulate the immune system locally, without inducing systemic immune suppression, and facilitate the monitoring of the response to the therapy following skin transplantation. Abstract : Microneedle arrays composed of hyaluronic acid and placed on skin allografts can locally deliver immunomodulators and simultaneously sample immune cells in interstitial fluid to monitor the response to the therapy. Using an allogeneic skin transplantation model, the microneedle‐mediated local delivery of the chemokine CCL22 and the cytokine IL‐2 is shown to increase local immune suppression in the allograft.